Pendalaman Materi dan Pelatihan Soal-Soal Olimpiade Bagi Guru SMP - Yohanes Ovaritus Jagom; Kristoforus Djawa Djong; Meryani Lakapu; Samuel Igo Leton; Irmina Veronika Uskono; Wilfridus Beda Nuba Dosinaeng (PELITA NUSA TENGGARA, 2026)
OSN is an activity that comprehensively develops a culture of learning, creativity, and motivation to achieve. However, the lack of knowledge among teachers and students about mathematics Olympiad questions has resulted in poor performance. The purpose of this community service activity is to equip teachers with basic skills and techniques in understanding Olympiad material so that they can guide students to acquire the skills to solve Olympiad questions. The methods used were lectures, discussions, and simulations. The results obtained from this activity were very effective, as demonstrated by an increase in the average score from 32.33 on the pretest to 85.67 on the posttest, indicating significant progress in mastery of concepts and basic skills in solving Olympiad questions. In addition to improving academic abilities, the results of the evaluation through questionnaires showed that participants were satisfied with the implementation of the activity, both in terms of material and delivery methods. Participants gained new insights and strategies in solving Olympic questions, which had an impact on increasing their confidence and motivation. Similar community service activities in the future need to be designed with a stronger focus on the basic understanding stage so that the results achieved can be more optimal and evenly distributed.